DAMAGE TO FRUITS AND VEGETABLES DURING STORAGE BY MUSHROOMS BELONGING TO DISEASE ALTERNARIAS (AGROINNOVATSIYА, 2024)
This article studied the occurrence of Alternaria blight in potatoes, cabbage and tomatoes in Uzbekistan, the distribution of Alternaria blight types and category criteria. Alternaria diseases are common on vegetable crops, on tomatoes - A. alternata, on potatoes - Alternaria solani, on carrots - A. brassicae and Altrernaria brassicola, on potato crops - Alternaria porri. A. cumerinum. It is also noted that Alternaria disease occurs when vegetable crops are stored in warehouses.